Enhancing Hotel Frontliner Professionalism Through Industry-Standard Grooming Training at Planet Holiday Hotel Batam - Supardi; Lubis, Arina Luthfini; Fatimah, Zahara; Wibowo, Andri (PUSLITABMAS-Politeknik Pariwisata Batamc, 2026)
This community service program was carried out in response to the increasing demands of professionalism in the hospitality industry, where frontliner appearance significantly affects guest impressions. Grooming is not only about physical appearance but also represents work ethics and service standards. The program took place at Planet Holiday Hotel Batam and involved five front office staff and 20 first-semester students from Batam Tourism Polytechnic. This activity aimed to improve frontliner grooming based on hotel industry standards. The method used was a combination of material presentation, practical demonstration, direct application, and group reflection. Each academic contributed to different roles such as proposal preparation, coordination with the hotel, training delivery, and discussion facilitation. The outcomes indicated a significant increase in participants' understanding, as shown in pre-test and post-test results. Hotel staff reported better awareness of grooming practices, while students expressed increased motivation and comprehension through hands-on learning. The session also promoted meaningful dialogue between academia and industry. Participants were highly enthusiastic, and the training environment was supportive and interactive. This success demonstrates the effectiveness of community service programs in bridging education and industry needs. Moreover, it opens up opportunities for future collaborations, such as structured internships or continuous professional training. The result of this program underscores the importance of experiential learning and cross-sectoral partnerships in preparing competent and industry-ready human resources. In conclusion, practical and collaborative models of community service like this provide a sustainable approach to workforce development and quality service improvement in hospitality.